2021
DOI: 10.52965/001c.24384
|View full text |Cite
|
Sign up to set email alerts
|

The dual degree orthopedic surgeon: A survey of the trends, motivations, and perceived value of the master of business administration degree

Abstract: Orthopedic ReviewsOrthopedic surgeons are obtaining Master of Business Administration (MBA) degrees at an increasing rate. This study aimed to identify the motivations, trends, and perceived value of the MBA degree for these dual degree surgeons. A total of 157 orthopedic surgeons with both MD and MBA degrees were surveyed with a 19-item questionnaire to identify surgeons' motivations for obtaining an MBA degree and the perceived value of the degree. A total of 66 responses (42%) were received. Most respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Plastic and orthopedic surgery had similar percentages (89%-96%) of male MD/MBAs while ophthalmology was lower at 80%. 6,7,10,11 This is similar to the gender composition of plastic and orthopedic surgery as a whole, with 83%, and 94% male predominance, respec- Abbreviations: MBA, Master of Business Administration tively. 13 By contrast, 57.5% of practicing ophthalmologists are male.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Plastic and orthopedic surgery had similar percentages (89%-96%) of male MD/MBAs while ophthalmology was lower at 80%. 6,7,10,11 This is similar to the gender composition of plastic and orthopedic surgery as a whole, with 83%, and 94% male predominance, respec- Abbreviations: MBA, Master of Business Administration tively. 13 By contrast, 57.5% of practicing ophthalmologists are male.…”
Section: Discussionsupporting
confidence: 59%
“…We reviewed two studies that disclosed salary information; surprisingly, 65% of the 83 surgeons included in these studies reported no change in salary. 6,7 This contradicts previous literature including a survey by Goldman that found the average starting salary of MD/MBAs to be $292,500 compared to $192,196 for non-MBA counterparts. 25 Similarly, Butcher and Hall reported a higher average starting salary for physicians who supplemented clinical work with leadership roles or business pursuits.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These include questions regarding the value of fellowship training, sex differences in surgeon income, and the value of further, nonorthopaedic education. [7][8][9] All studies of this type have the same inherent limitation: In the absence of near-perfect survey completion or nuanced demographic considerations, these polls suffer from selection bias. Nevertheless, these surveys provide the best insight, to date, regarding topics elusive to objective study.…”
Section: Discussionmentioning
confidence: 99%